Information Infrastructures within European Health Care Working with the Installed Base - Aanestad, Margunn; Grisot, Miria; Hanseth, Ole; Vassilakopoulou, Polyxeni (Health Informatics, 2017)
e-prescription; information systems design; infrastructure; public; patient- oriented web platforms